Control y valoración de inventario según la NIC 2 en el GAD Municipal del Cantón Vinces periodo enero - diciembre del 2023. - Olvera Mosquera, Ingrid Briggitt (2024)
This document corresponds to the preparation of a case study carried out by the Municipal GAD of the Vinces canton, its central theme: inventory control and valuation according to IAS 2 in the municipal GAD of the Vinces canton period January - December 2023, whose objective en Analyze the control and valuation of inventory according to IAS 2. The need arises because the institution has an inventory record but does not use it appropriately. The importance of this study lies in improving this institution in terms of inventory registration. The methodology is supported with the qualitative paradigmatic modality. The data provided was analyzed and evaluated through an interview. The types of research used for this research were exploratory, descriptive and bibliographic, supported by the inductive method and a question guide was used as tools. The research line is supported by financial, administrative, tax, audit and control management, followed by the audit and control sub-line. The results obtained mention that the institution subject to the investigation has not correctly complied with the inventory information system, for this reason this institution has shortcomings in that area.